1998
DOI: 10.1136/bjo.82.3.225
|View full text |Cite
|
Sign up to set email alerts
|

Recovery in microtropia: implications for aetiology and neurophysiology

Abstract: Aims/background-The basis of binocular single vision in microtropia remains a matter of contention. This paper discusses the implications of recovery, in a group of primary microtropes following treatment, in relation to current concepts on the aetiology of the condition and proposed retinocortical correspondence. Methods-Nine previously untreated primary microtropes whose condition resolved, were reviewed in detail to assess the patterns of change in retinal correspondence, uniocular fixation, stereoacuity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 34 publications
(25 reference statements)
1
14
0
Order By: Relevance
“…In addition, they used the Titmus test, which has monocular clues that may reduce the accuracy of the results. Cleary and colleagues 15 reported improvement of binocular function in a prospective study, which, however, was mainly 2.9 AE 0.9 (1-6.5)…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, they used the Titmus test, which has monocular clues that may reduce the accuracy of the results. Cleary and colleagues 15 reported improvement of binocular function in a prospective study, which, however, was mainly 2.9 AE 0.9 (1-6.5)…”
Section: Discussionmentioning
confidence: 94%
“…12 Occlusion therapy and atropine further improved the outcome when refractive correction alone was not satisfactory. 13,14 Several studies have reported that binocular function can be improved with improvement of visual acuity [15][16][17] ; however, most of these were retrospective studies, [17][18][19] and they included a variety of patients including those with strabismus. [15][16][17] This study aimed to evaluate the degree of improvement of binocular function among previously untreated anisometropic children and to identify the factors that affect the degree of improvement.…”
mentioning
confidence: 98%
“…Cleary et al (1998) reported recovery in microtropia with improved stereopsis. The current study was not designed with a phase of refractive adaptation followed by a phase of occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Recently the PEDIG (Cotter et al 2012) completed a clinical trial that evaluated optical treatment of strabismic and combined strabismic-anisometropic amblyopia; after 18 weeks, they found resolution of amblyopia in about a quarter of the children before initiating patching. However, Cleary et al (1998) reported that occlusion combined with spectacle correction in strabismic amblyopia seems more effective than spectacle correction alone.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The prevalence of micro-esotropia in several large series of primary and secondary microtropia has been reported from 61% to 90%. [4][5][6][7] None of these studies reported a single case of monofixational hypertropia, suggesting an extremely low prevalence of this form of small angle strabismus.…”
Section: Introductionmentioning
confidence: 95%